Understanding why mother can lose child custody in Malaysia - Kadir, Rokiah; Abdullah, Raihanah; Mokhlis, Safiek (UUM College of Law, Government and International Studies, 2021)
Custody decisions are tailored to the circumstances of each case based on related principles with the protection of child welfare as the courts’ paramount consideration. This paper sought to understand custody issues from the quantitative viewpoint through a conceptual model and examined how child custody principles have influenced loss decisions for mothers. The methodology used was content analysis and the Chi-Square correlation, with usable data provided by 47 cases decided in Malaysia between 1987 and 2017 based on Act 303. A coding instrument and a conceptual framework were developed with items covering the presumption of maternal custody, custodian qualification and loss of rights, and the child’s and the mother’s wishes. The findings revealed that mothers were less likely to lose custody cases, and when they did, their defeats were strongly influenced by factors related to children’s preferences and the status quo arrangement. The results contribute to an understanding of how mothers can lose custody of their children, and clarify whether some of the independent variables are used more regularly and are more predictive of the loss decisions than the others.